Isotype-specific regulation of human lymphocyte production of immunoglobulins by sustained exposure to vasoactive intestinal peptide - Hassner, Avi; Lau, Matthew S.; Goetzl, Edward J.; Adelman, Daniel C. (Journal of allergy and clinical immunology, 1993)
Exposure of lymphocytes to nanomolar to micromolar concentrations of vasoactive intestinal peptide (VIP) for 1 to 3 days only modestly suppressed or enhanced the production of IgA and IgM, but not IgG. The effects of twice daily additions of 10 −12 to 10 −7 mol/L VIP for up to 18 days on pokeweed mitogen- stimulated peripheral blood mononuclear cells (PBMCs) from normal human subjects was examined by quantifying the production of IgG, IgM, and IgA. The maximum suppression of IgG by 10 −9 mol/L VIP was 79% ± 33% (mean ± SD) (range, 41 % to 97%; p < 0.015) on day 9 and 84% ± 1 % (range, 74% to 96%; p < 0.0001) on day 14 and was significant at 6 × 10 −10 to 4 × 10 −9 mol/L VIP. Suppression of IgM production by 10 −9 mol/L VIP was significant and was observed first on day 5 and persisted through day 14. VIP did not alter IgA production or affect the proliferation or viability of PBMCs. The production of IgE by interleukin-4 stimulated PBMCs was enhanced consistently in two subjects but not in two other subjects. The duration of exposure to nanomolar concentrations of VIP is thus a critical determinant of its immunoregulatory effect, as manifested by late suppression of production of IgG and IgM and concurrent enhancement of production of IgE in some subjects.